Biogas Production from Vegetables and Fruit Wastes Using Anaerobic Floating Bioreactor - soeprijanto soeprijanto; Anfi Reynikha Fatullah; Sashi Agustina; Dyah Firdha Amalia; Alif Adi Kaisar (Eksergi, 2020)
Markets and supermarkets are one of the pillars of the country's economy, besides that, they are also the biggest contributors to vegetable and fruit waste which can cause various environmental problems. Therefore, the abundance of vegetable and fruit waste produced by markets and supermarkets can be utilized as environmentally friendly alternative energy, namely biogas. This study aimed to determine the effect of organic loading rate (OLR) on biogas production and gas composition in a continuous anaerobic floating bioreactor using mixed vegetable and fruit waste. A 40-l anaerobic floating bioreactor was utilized and the hydraulic retention time was 10 days; one kg of vegetable and fruit wastes at a 1:1 mass ratio was added with water to 4 l and introduced during 25 days; the daily biogas production was collected in a floating drum and measured as volume. The maximum biogas yield was 0.0452 m3/kg, achieved using the OLR of 0.0125 kg/l.day.  The use of OLR of 0.0250, 0.0375 and 0.0500 kg/l.d reached biogas yields of 0.0435, 0.0282, and 0.0163 m3/kg, respectively. The composition of the maximum biogas yield was 68.17% CH4, 19.34% CO2, 1.85% H2S, and 0.64% NH3.